Multidisciplinary management of head and neck cancer: First expert consensus using Delphi methodology from the Spanish Society for Head and Neck Cancer (part 1). (July 2017) - Mañós, M.; Giralt, J.; Rueda, A.; Cabrera, J.; Martinez-Trufero, J.; Marruecos, J.; Lopez-Pousa, A.; Rodrigo, J.P.; Castelo, B.; Martínez-Galán, J.; Arias, F.; Chaves, M.; et al.
Highlights: Spanish Multidisciplinary consensus on squamus cell neoplasm os the head and neck. Multidisciplinary approach for larynx/hypopharynx tumors. Multidisciplinary approach for oral cavity/oropharynx tumors. Abstract: Head and neck cancer is one of the most frequent malignances worldwide. Despite the site-specific multimodality therapy, up to half of the patients will develop recurrence. Treatment selection based on a multidisciplinary tumor board represents the cornerstone of head and neck cancer, as it is essential for achieving the best results, not only in terms of outcome, but also in terms of organ-function preservation and quality of life. Evidence-based international and national clinical practice guidelines for head and neck cancer not always provide answers in terms of decision-making that specialists must deal with in their daily practice. This is the first Expert Consensus on the Multidisciplinary Approach for Head and Neck Squamous Cell Carcinoma (HNSCC) elaborated by the Spanish Society for Head and Neck Cancer and based on a Delphi methodology. It offers several specific recommendations based on the available evidence and the expertise of our specialists to facilitate decision-making of all health-care specialists involved.